KONSEP PENDIDIKAN IKHWAN AL-SHAFA DAN RELEVANSINYA DENGAN DUNIA POSTMODERN - Rahman Afandi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2019)
Abstract: The Ikhwan al-Shafa is an organization established by a group of people (mujtahidin) consisting of philosophers, who focused their attention on the field of da'wah and education, that developed at the end of the second century Hijrah in the city of Basra, Iraq. It is a discussion and teaching forum. In general, its emergence is motivated by concerns about the implementation of Islamic teachings that have been contaminated by teachings from outside Islam at that time, and to revive love for science among Muslims. They compiled 51 agreements known as the